Akibat Yang Ditimbulkan Dari Adanya Perselisihan Dan Pertengkaran Terus Menerus Dalam Rumah Tangga - Abdul Rahman Masionu (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This research aims to determine the extent of the impact caused by arguments in the household resulting in divorce. To find out, the author uses normative empirical research methods. Divorce is a legal event that results in the legal termination of a marriage between a husband and wife whose legal process is carried out in court. The factors that cause continuous disputes and quarrels that trigger divorce at the Tilamuta Religious Court, Baolemo Regency are: (a) Economic problems. (b) Third party interference. (c) Polygamy is unhealthy. (d) Domestic violence/abuse occurs. Divorce will certainly have an effect on both parties and their descendants. The consequences that arise from continuous disputes and quarrels include: (a) Disruption in fulfilling the rights and obligations of husband and wife, (b) problems regarding child custody, (c) division of joint assets, lack of control of each other's egos. each and coupled with the husband not being able to control his emotions so he takes it out on his wife.